2019
DOI: 10.4103/ija.ija_310_19
|View full text |Cite
|
Sign up to set email alerts
|

Role of erector spinae plane block versus paravertebral block in pain control after modified radical mastectomy. A prospective randomised trial

Abstract: Background and Aims:Thoracic paravertebral block (TPVB) provides effective analgesia in breast surgery. Recently, use of erector spinae plane block (ESPB) in controlling post-operative pain has proved effective. This study aimed to compare the effect of ESPB with TPVB in post-mastectomy acute pain control.Methods:A prospective, randomised double-blinded study enrolled 70 adult female patients, scheduled for modified radical mastectomy. Patients were randomised into two groups, receiving 20 ml of 0.25% bupivaca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
83
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 28 publications
1
83
0
3
Order By: Relevance
“…In the study of Gad et al, pain score and the frequency of analgesics use in the SEP group was higher than in the Pecs group, which was consistent with the results of the present study (16). A clinical trial by Ghamry and Amer (17) aimed at examining the role of erector spinae plane block (ESPB) versus paravertebral block in the control of postoperative pain after mastectomy showed no significant difference in pain score between the two groups within 24 hours (2,4,6). No pain was reported at 8, 12, 18, and 24 hours after surgery, and pain intensity began to increase at 3 to 6 hours after surgery, and pain intensity was significantly different between the two groups at 6 hours after surgery (17).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the study of Gad et al, pain score and the frequency of analgesics use in the SEP group was higher than in the Pecs group, which was consistent with the results of the present study (16). A clinical trial by Ghamry and Amer (17) aimed at examining the role of erector spinae plane block (ESPB) versus paravertebral block in the control of postoperative pain after mastectomy showed no significant difference in pain score between the two groups within 24 hours (2,4,6). No pain was reported at 8, 12, 18, and 24 hours after surgery, and pain intensity began to increase at 3 to 6 hours after surgery, and pain intensity was significantly different between the two groups at 6 hours after surgery (17).…”
Section: Discussionsupporting
confidence: 91%
“…In the study of Ghamry and Amer, there was no significant difference between the two groups in terms of postoperative morphine use (17). Altiparmak et al in their study also showed that morphine use decreased by up to 65% in the ESPB group within 24 hours after surgery, although there was no difference in the severity of pain between the two groups (21).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These findings are consistent with the results of previous studies. 11,13 Gürkan et al compared 3 groups of patients who received ESPB, TPVB or no intervention before unilateral breast surgery and found that morphine consumption for 24 h postoperatively was similar between both block groups, but was significantly smaller in both block groups compared with the control group. 11 Although we found that the two blocks were comparable regarding our primary outcomes, the results of our secondary outcomes suggest that the two blocks do not act similarly.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] However, whether ESPB has similar analgesic effects to TPVB for breast surgery is still inconclusive. 11,13,14 Moreover, information on sensory blockade after ESPB is still mostly limited in case reports. [15][16][17] Injectate administered by ESPB is expected to make a wide spread in the craniocaudal direction, yet the results of cadaveric studies show inconsistent and unpredictable dye spread with little spread to the paravertebral space.…”
Section: Introductionmentioning
confidence: 99%